ANALYSIS OF HOSPITAL MANAGEMENT INFORMATION SYSTEMS (HMIS) ON THE EFFECTIVENESS AND EFFICIENCY OF OUTPATIENT SERVICES AND ITS IMPLICATIONS FOR EMPLOYEE PERFORMANCE (A SURVEY STUDY AT RUMAH SEHAT TERPADU DOMPET DUAFA HOSPITAL, BOGOR CITY) - Anggilia Yuliani Susanti; Sri Rochani Mulyani; Rukhiyat Syahidin; Ayu Laili Rahmiyati; Farida Yuliaty; Fitriana (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of the Hospital Management Information System (HMIS) on the effectiveness and efficiency of outpatient services and its implications for employee performance at Rumah Sakit Sehat Terpadu Dompet Dhuafa, Bogor City. The study employed a quantitative approach with a survey method involving employees directly engaged in outpatient services and HMIS utilization. Data were collected through questionnaires and analyzed using descriptive analysis and path analysis with SPSS version 24. The results indicate that HMIS contributes to service effectiveness (β=0.605; R²=36.6%), reflected in improved patient data accessibility, recording accuracy, and service speed. HMIS also contributes to service efficiency (β=0.603; R²=36.4%), evidenced by reduced patient waiting times and accelerated administrative processes. Service effectiveness and efficiency jointly contribute to employee performance (R²=26.5%), although only efficiency demonstrates a meaningful partial contribution. HMIS exerts a direct effect on employee performance (β=0.526) as well as indirect effects through effectiveness (0.126) and efficiency (0.242), yielding a total effect of 0.894. It is concluded that optimal HMIS implementation contributes to improving outpatient service quality and employee performance.